Models of field-aligned currents needful to simulate the substorm variations of the electric field and other parameters observed by EISCAT - M. A. Volkov; A. A. Namgaladze; A. A. Namgaladze (Annales Geophysicae, 1996)
We have used the global numerical model of the coupled ionosphere-thermosphere-protonosphere system to simulate the electric-field, ion- and electron-temperature and -concentration variations observed by EISCAT during the substorm event of 25 March 1987. In our previous studies we adopted the model input data for field-aligned currents and precipitating electron fluxes to obtain an agreement between observed and modelled ionospheric variations. Now, we have calculated the field-aligned currents needful to simulate the substrom variations of the electric field and other parameters observed by EISCAT. The calculations of the field-aligned currents have been performed by means of numerical integration of the time-dependent continuity equation for the cold magnetospheric electrons. This equation was added to the system of the modelling equations including the equation for the electric-field potential to be solved jointly. In this case the inputs of the model are the spatial and time variations of the electric-field potential at the polar-cap boundaries and those of the cold magnetospheric electron concentration which have been adopted to obtain the agreement between the observed and modelled ionospheric variations for the substorm event of 25 March 1987. By this means it has been found that during the active phase of the substorm the current wedge is formed. It is connected with the region of the decreased cold magnetospheric electron content travelling westwards with a velocity of about 1 km s–1 at ionospheric levels.